Diabetic peripheral angiopathy treatment using a multi-laser therapy device - Y. Zabulonov; O. Chukhraiyeva; A. Vladimirov; M. Chukhraiyev; W. Zukow (Kazimierz Wielki University, 2015)
Zabulonov Y., Chukhraiyeva O., Vladimirov A., Chukhraiyev M., Zukow W. Diabetic peripheral angiopathy treatment using a multi-laser therapy device. Journal of Education, Health and Sport. 2015;5(10):227-233. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.32801 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2810%29%3A227-233 https://pbn.nauka.gov.pl/works/662978 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2015. Revised 05.09.2015. Accepted: 20.10.2015.   616.711:615.846+615.837.3 DIABETIC PERIPHERAL ANGIOPATHY TREATMENT USING A MULTI-LASER THERAPY DEVICE   Zabulonov Y.1, Chukhraiyeva O.1, Vladimirov A1., Chukhraiyev M.1, Zukow W.2   1Public Organization "Ukrainian Society of Physical and Rehabilitative Medicine", Kiev, Ukraine 2Faculty of Physical Education, Health and Tourism, Kazimierz Wielki University, Bydgoszcz, Poland   Summary   The results of research on the effectiveness of multifunctional laser therapy treatment of diabetic peripheral arterial disease in patients with type 2 diabetes on the basis of a systematic approach. The clinical picture of peripheral angiopathy consists of a combination of specific diabetic angiopathy with the medium and large vessels atherosclerosis. In the case of diabetes feet the combined lesions are underlying the obliterating vascular disease. In younger diabetic patients these changes have primarily functional nature in the form of changes in vascular tone and capillaropathy. Thus, there is a need to develop efficient way to treat and prevent DPA that could actively influence the quality of life, reduce or prevent complications that arise during DPA and lower doses of pharmaceuticals. Nowadays we know several ways of physiotherapeutic treatment and prevention of complications of diabetes. Almost all patients after 3-4 sessions have a slight improvement of blood microcirculation in the lower extremities and reduce overall blood sugar level. After 10-12 treatments the test scores improve. The closest to the developed method is a method of treating diabetes and its complications prevention, which includes magnetic-laser-ultrasound therapy of the pancreas, liver and their segmental zones. This magneto-laser-ultrasound therapy treatment is combined with low-intensity electromagnetic radiation physiopuncture in a millimetric range spectrum [2]. The main drawbacks of existing methods of treating complications of diabetes is that they do not involve zonal influence on the DPA area and do not include the need to influence the oxygen capacity of  blood and increase its energy activity, and in this regard, the effectiveness of the treatment is generally reduced. As the base of invention is laid the task of creating such a way that dramatically improves the performance of DPA treatment in patients with diabetes and reduces the procedural burden on them. Our developed method of treating the DPA in diabetic patients is based on the simultaneous use of magnetic laser stimulation of the pancreas or liver with additional simultaneous laser irradiation of venous blood in popliteal areas and scanning laser beam therapy of the DPA area. Procedures performed 2-3 times a week. The course of treatment is 10 procedures. A second course is performed if necessary after 1-2 months. There may be some tactical changes, which are determined individually by your doctor depending on the clinical condition of the patient. The technical results, achieved by suggested solution are: increasing the effectiveness of treatment, the removal of metabolic disorders, a positive effect on the microcirculation, desintoxication of the body, increasing blood oxygen capacity and increase of its energy activities, which largely prevents complications in the treatment of DPA. Based on the proposed method treatment is performed using a laser multifunction system. Magnetic-laser stimulation of the pancreas and liver is performed, for example, using the following parameters: modulation frequency of magnetic laser - 9.4 Hz, magnetic fields up to 30 ± 10 mT, the optical flow power of red or blue range of the spectrum is 30 ± 10Wt, optical flow power of  infrared spectrum  - of 50±20 mW, magnetic laser applicator of  red spectral range is set on the projection of the pancreas, magnetic laser applicator of infrared or blue range of the spectrum is set on the projection of the liver. Popliteal overvessel blood laser irradiation is performed using the laser emission of red spectrum range - wavelength laser 0,63 ± 0,03 mm, laser power - 20±10 mW. The DPA zones therapy with the laser scanning beam: laser wavelength - 0,63±0,03 mm, laser power - 150±50 mW, scanning figure - "Grid", the scanning dimensions - 400x200 mm. Additionally it is possible to perform nasal breathing with SOM using apparatus MIT-S. After the procedure is done the patient ingests the 50-200 ml of activated by singlet-oxygen mixture fluid. The liquid activation is held for 3 minutes. As can be seen from the data in Table 1, the patient significantly improved metabolism indicators and clinical parameters (blood pressure, pulse, bowel function, etc.). The developed method can be used in hospitals, clinics, spa facilities and therapeutic centers, etc. and be combined with drug therapy.   Key words: diabetic peripheral angiopathy, a multi-laser therapy device.